Knowledge and Practice of informed Consent among Nurses in Specialist Hospital Bauchi, Bauchi State - Salisu Umar Muhammad; MUHAMMAD Maryam Musa; MUHAMMAD Maimuna; FATIMA MUHAMMAD DAMBAM; SULEMAN AHMED WAN (RADINKA JAYA UTAMA PUBLISHER, PADANG, INDONESIA, 2026)
The implementation of informed consent is a fundamental cornerstone for protecting patient rights and ensuring ethical nursing practice. This study aimed to assess the level of knowledge and clinical practice regarding informed consent among nurses at specialist hospital Bauchi, Nigeria. Utilizing a cross-sectional descriptive survey design, data were collected from 87 nurses selected through convenience sampling. The research instrument consisted of a structured questionnaire, which was validated and tested for reliability, with data subsequently analyzed using descriptive statistics via SPSS Version 29. The results indicated that the nurses possessed a relatively high level of knowledge concerning the legal and ethical dimensions of informed consent, including a robust understanding of patient mental competence and risk disclosure. In clinical practice, the majority of nurses were found to regularly explain medical procedures and maintain documentation according to established standards. However, significant gaps persisted in the consistency of explaining alternative procedures and facilitating family involvement, both of which were practiced by less than 50% of the respondents. Key barriers identified in this study included language barriers, inadequate communication skills, excessive workloads, and severe time constraints. The study concludes that while nurses demonstrate adequate theoretical knowledge, systemic and interpersonal challenges continue to hinder the consistency of informed consent procedures. These findings underscore the necessity for targeted managerial interventions and professional development to optimize nursing practice within the healthcare system of Northern Nigeria.